A Self‐Powered Smart Roller‐Bearing Based on a Triboelectric Nanogenerator for Measurement of Rotation Movement. Issue 12 (24th August 2018) - Choi, Daehwan; Sung, Taehoon; Kwon, Jang‐Yeon
Abstract: Triboelectric nanogenerator technology is one of the most promising technologies with great potential for applications in self‐powered electronics and sensing systems. Herein a simply fabricated, cost‐effective, triboelectric sensor with a roller‐bearing structure which is composed of rollers and electrode is presented. Based on the triboelectric effect, this smart bearing generates the output electrical signals in response to rotation movement or displacement of an object mounted with the bearing. The triboelectric sensor delivers an open‐circuit voltage of ≈45 V and a short‐circuit current of ≈6 µA at a rotation rate of 400 r min −1 . Using the output signals of the smart bearing, the angular velocity and position as well as damage in the components can be continuously monitored. Furthermore, the smart bearing mounted to the steering wheel can be utilized as an energy harvester, a rotation direction detector, and a driving style sensing system at the same time. This work greatly expands the applicability of triboelectric nanogenerators as self‐powered sensing systems. Abstract : A self‐powered smart roller‐bearing based on a triboelectric nanogenerator for rotation angle measurement is demonstrated. This smart bearing generates the output electrical signals in response to rotation movement or displacement of an object mounted with the bearing.